THE EFFECT OF ADVERTISING, BRAND TRUST, AND BRAND IMAGE TO PURCHASE INTENTION (A STUDY ON INDIHOME INDONESIA CUSTOMERS IN MALANG) - PRAKOSO, HARLEYANTO DIBYO (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
This study aims to examine the effect of advertising, brand trust, and brand image toward purchase intentionof Indihome customer in Malang. The research is explanatory research, which explains the causalrelationship between the variables through hypothesis testing. The data collection technique of this studyuses questionnaires. This study used 150 samples who ever used Indihome product. The sampling technique used was purposivesampling and the research instruments were tested using the validity test, reliability test, hypothesis test,Partial Linear Square (PLS) analysis technique to analyze the data. The result from this study showed thatthe variable of advertising, brand trust, and brand image provides good value, and each of them made apositive and significant effect on purchase intention.Keywords: Advertising, Brand Trust, Brand Image, and Purchase Intention.Â